Electric or Internal Combustion Engines for Passenger Cars? - Environmental and Economic Aspects - Zoran Čekerevac; Zdeněk Dvořák; Lyudmila Prigoda (Communications, 2022)
The paper is focused on fuels, their users - engines and the end-user, the vehicles, from an environmental and economic point of view. The basic characteristics of potential fuels for internal combustion engines, as well as possible sources of electricity, are analysed. A comparative analysis of characteristics of vehicle propulsion with gasoline, diesel fuel, compressed natural gas, liquefied petroleum gas and electricity was performed. The research has shown that the application of vehicles with an electric motor is ecologically justified only in cases of obtaining electricity in an environmentally friendly way and that in other cases there is no profit in an ecological sense. From an economic point of view, if there were no subsidies to manufacturers and buyers of electric cars, they would not be competitive with internal combustion engines now. Within the research, potential solutions for reducing air pollution and improving the quality of life in cities have been proposed.